PERAN KEGIATAN KEAGAMAAN TERHADAP PEMBENTUKAN AKHLAK SISWA KELAS VI - Nurmayani, Nurmayani; Gilang Fathir Andikha; Fathia Azzahra Nazfa; Riski Fatma Sofi Nasution; Shalsya Nazyfha; Yuricha Nadwa At tazkia Rambe (Jurnal Merah Putih Sekolah Dasar, 2025)
School religious activities play a vital role in shaping students’ morality from an early age. This research aims to analyze the influence of religious activities (such as collective prayer, congregational prayer, and religious studies) on the moral development of sixth-grade students at SD IT Al Hijrah 2. Using a descriptive qualitative method, data was collected through interviews and documentation with the class teacher as the main subject. The results indicate that religious activities have a significant impact on instilling values of discipline, responsibility, and respect. Teachers primarily employ the methods of exemplary behavior, habituation, and storytelling as key strategies for moral education. The main challenges encountered include students’ lack of consistency in applying moral values outside of school, the negative influence of gadgets and social media, and variations in parental support. It is concluded that religious activities serve as a moral fortress for students, but their effectiveness highly relies on the synergy between the school, teachers, and parents.